PATTERNS AND TIME OF PERMANENT TEETH ERUPTION IN THE GOMBE STATE CHILDREN AND ADOLESCENCES - RAYYANU Z. S; ALIYU N. B; MUHAMMAD M. I (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
The study aims to determine the time, sequence, gender differences, and pattern of permanent teeth eruption in Gombe State children and Adolescences. The total number of 300 individuals with an equal number of males (n=150) and females (n=150) with ages ranges from 5-14 years from Government day Secondary and Primary School Lijji were randomly selected for this research. The data was collected with the subject sited on a chair under sunlight. The oral examination was carried out using a mouth mirror, hand gloves, and a blunt probe. The teeth were cleaned of food debris with cotton wool for proper visibility. The status of the eruption of each permanent tooth was recorded even if a small part of the crown is visible clinically penetrating the oral mucous membrane. It is regarded as erupted and recorded accordingly, except for third molars. The obtained data were subjected to Student - t-test to obtain differences in the pattern of permanent teeth eruption using SPSS version 20.0 software (IBM Corporation, USA). The result shows that in the five years age group, none of the permanent teeth had erupted in both males and females. In the age group of 14 years, all the permanent teeth except the third molars had erupted, among which the maxillary teeth erupted earlier in males than females; likewise the mandible teeth erupted earlier in males than in females.